Recommendation of non-destructive sampling method for density estimation of the eucalyptus wood - Franciane Andrade de Pádua; João Otávio Poletto Tomeleri; Mariana Pires Franco; José Reinaldo Moreira da Silva; Paulo Fernando Trugilho (Maderas: Ciencia y Tecnología, 2019)
This study aimed to determine the wood density using destructive and non-destructive sampling methods in a eucalypt hybrid clonal and determine the best point for the non-destructive sampling of the tree. A 5.6-year-old Eucalyptus urophylla x Eucalyptus grandishybrid clone, from an energetic forest, was used, planted in the municipal district of Martinho Campos, MG, Brazil. The trees were sampled by three methods of destructive sampling. The traditional method (0%, 25%, 50%,75% and 100% of the commercial height Hc); alternative method (2%, 10%, 30% and 70% Hc) and via a meter by meter method starting from a height of 1.30 m from the soil (DBH). Three non-destructive sampling methods were also appraised: Resistograph®, Pilodyn® and 22 mm diameter cores at a DBH. The use of the Resistograph® at the 1.10 m or 1.50 m points and the Pilodyn® at 1.50m of height from the soil results the best correlations with the basic density determined by the three destructive sampling methods considered.